Liberia : Request for an Extension of the Arrangement Under the Extended Credit Facility-Staff Report and Press Release. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Liberia's Request for an Extension of the Arrangement Under the Extended Credit Facility (ECF). From mid-2014 to mid-2015, Liberia faced a serious Ebola virus disease crisis, which triggered the declaration of a state of emergency. End-June 2014 performance criteria (PCs) and indicative targets were met, except the revenue floor and the floor net foreign exchange position of the Central Bank of Liberia (CBL), and the ceiling on net domestic assets. The authorities are expected to request waivers for the missed PCs in light of corrective actions undertaken to improve revenue collection and strengthen the net foreign exchange position of the CBL. The IMF staff supports the authorities' request to extend the ECF arrangement.